PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BTPN SYARIAH MMS CILEUNGSI BOGOR - Nuraida Putri; Intan Sari Budhiarjo (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of workload and work discipline partially or simultaneously on employee performance at BTPN Syariah MMS Cileungsi Bogor. This type of research is associative quantitative. The analytical methods used in this research are instrument tests, classical assumption tests, descriptive analysis, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, coefficient of determination tests, hypothesis tests. The population in this study were BTPN Syariah MMS Cileungsi Bogor employees using a saturated sample of 55 respondents. Based on the results of hypothesis testing related to Workload (X1), it is obtained that tcount = -6.265 > ttable = 2.006 with sig 0.000 <0.05, then Ho is rejected and Ha is accepted, this can be partially concluded that there is a negative and significant influence between Workload on Employee Performance At BTPN Syariah MMS Cileungsi Bogor. Meanwhile, the results of hypothesis testing related to Work Discipline (X2) obtained tcount = 5.939 > ttable = 2.006 with sig 0.000 < 0.05, then Ho is rejected and Ha is accepted, this can be partially concluded that there is a positive and significant influence between Work Discipline on Employee Performance At BTPN Syariah MMS Cileungsi Bogor. Then, the results of the hypothesis test Fcount = 38.867 > Ftable = 3.175, so Ho is rejected and Ha is accepted. So it can be concluded that simultaneously there is a positive and significant influence between Workload and Work Discipline on Employee Performance at BTPN Syariah MMS Cileungsi Bogor.